Particle Ratios from Strongly Interacting Hadronic Matter - Waseem Bashir; Saeed Uddin; Hamid Nanda (Advances in High Energy Physics)
We calculate the particle ratios K+/π+, K-/π-, and Λ/π- for a strongly interacting hadronic matter using nonlinear Walecka model (NLWM) in relativistic mean field (RMF) approximation. It is found that interactions among hadrons modify K+/π+ and Λ/π- particle ratios, while K-/π- is found to be insensitive to these interactions.